Management discourse: Talking the power walk in organizational communication - Norlyk, Birgitte (Language at Work - Bridging Theory and Practice, 2009)
How does management talk the power walk in organizations? By giving straightforward orders since this is a traditional managerial prerogative which does not require an understanding of the subtleties of discourse and the finer aspects of interpersonal communication? Or should management avoid potentially face-threatening orders and concentrate on subtle and discreet manifestations of power in which discourse becomes an important tool when communicating with internal and external stakeholders?